2016
DOI: 10.1186/s12985-016-0472-z
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of H9N2 avian influenza virus exposure among poultry workers from Fars province of Iran

Abstract: BackgroundSince the 1990s, influenza A viruses of the H9N2 subtype have been causing infections in the poultry population around the globe. This influenza subtype is widely circulating in poultry and human cases of AI H9N2 have been sporadically reported in countries where this virus is endemic in domestic birds. The wide circulation of H9N2 viruses throughout Europe and Asia along with their ability to cause direct infection in mammals and humans, raises public health concerns. H9N2 AI was reported for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
0
34
1
1
Order By: Relevance
“…The first human infections caused by H9N2 was reported in 1999, Hong Kong. Prevalence of H9N2 in Iran was reported 17%‐18% . These subtypes have repeatedly been isolated from patients in China and Hong Kong .…”
Section: Discussionmentioning
confidence: 99%
“…The first human infections caused by H9N2 was reported in 1999, Hong Kong. Prevalence of H9N2 in Iran was reported 17%‐18% . These subtypes have repeatedly been isolated from patients in China and Hong Kong .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the prevalence of H9N2 virus was rather constant and the virus repeatedly emerged in the human population (Heidari et al., ; Huang et al., ). The changes in viruses may be the result of the widespread circulation and the lack of adequate surveillance and control programs.…”
Section: Introductionmentioning
confidence: 99%
“…exposed to infected birds as well as the general population within H7N9 virus-affected regions in China showed overall low seropositivity indicating a low number of transmission events causing subclinical human infections Lin et al, 2016;Liu et al, 2016). In Iran, poultry workers were positive for H9N2 virus while the seroprevalence of nonexposed individuals for both H9N2 strains were significantly lower (Heidari et al, 2016). One study indicated that occupational exposure to chicken flocks was an important risk factor for H9N2 infection (Wang et al, 2014), while others showed seroprevalence estimates against H9 that were significantly higher in live poultry market workers, large-scale poultry farmers and backyard farmers than in poultry slaughtering factory workers and wild bird habitat workers .…”
Section: Handling and Manipulationmentioning
confidence: 99%